2018
DOI: 10.3389/fnagi.2018.00191
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Vascular Imaging Biomarkers in Down Syndrome Provide Unique Insights Into Brain Aging and Alzheimer Disease Pathogenesis

Abstract: People with Down syndrome (DS) are at high risk for developing Alzheimer disease (AD). Neuropathology consistent with AD is present by 40 years of age and dementia may develop up to a decade later. In this review, we describe metabolic and vascular neuroimaging studies in DS that suggest these functional changes are a key feature of aging, linked to cognitive decline and AD in this vulnerable cohort. FDG-PET imaging in DS suggests systematic reductions in glucose metabolism in posterior cingulate and parietote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…In the neurotypical AD population, we have identified a pro‐inflammatory endophenotype that identifies a specific subset of AD patients who benefitted from a “failed” nonsteroidal anti‐inflammatory drug (NSAID) trial 28 . It appears that this pro‐inflammatory endophenotype is also present within DS adults with MCI and AD, which is consistent with the increased role of inflammation among individuals with DS 46,47 . Prior work has shown that neuroinflammation is upregulated in fetal development in DS, which may accelerate the development of AD pathology 46 .…”
Section: Discussionsupporting
confidence: 58%
“…In the neurotypical AD population, we have identified a pro‐inflammatory endophenotype that identifies a specific subset of AD patients who benefitted from a “failed” nonsteroidal anti‐inflammatory drug (NSAID) trial 28 . It appears that this pro‐inflammatory endophenotype is also present within DS adults with MCI and AD, which is consistent with the increased role of inflammation among individuals with DS 46,47 . Prior work has shown that neuroinflammation is upregulated in fetal development in DS, which may accelerate the development of AD pathology 46 .…”
Section: Discussionsupporting
confidence: 58%
“…The peripheral alterations presented above in this review suggest that DS subjects might be potentially more susceptible to developing brain insulin resistance than other children. Indeed, growing evidence highlight the role of metabolic defects as a risk factor for cognitive impairments also in DS (Caracausi et al, 2018;Head et al, 2018;Vacca et al, 2019).…”
Section: Brain Insulin Resistance Is a Feature Of Down Syndromementioning
confidence: 99%
“…With regard to brain alterations, accumulation of toxic catabolites (Caracausi et al, 2018;Gross et al, 2019) or dysfunction of key metabolic pathways were identified as crucial determinants triggering neuronal dyshomeostasis and neurodegeneration in DS (Head et al, 2018;Lott and Head, 2019;Vacca et al, 2019).…”
Section: Brain Insulin Resistance Is a Feature Of Down Syndromementioning
confidence: 99%
“…Markers of AD‐specific neurodegeneration include regional hypometabolism on FDG PET9 86‐88 or hippocampal atrophy 89‐91 have been studied in DS and parallel findings from the sporadic and autosomal dominant forms of AD. More recently, plasma neurofilament light chain (NfL) levels (also a marker of neurodegeneration) have been shown to correlate with clinical status of AD in DS 92 as well as standard AD biomarkers such as amyloid PET and tau PET 93 .…”
Section: Biomarker Assessments Of Amyloid Tau and Neurodegenerationmentioning
confidence: 99%